Scale Prevention Technique to Minimized Scaling on Re-Injection Pipes in Dieng Geothermal Field, Central Java Province, Indonesia - Agustinus, Eko Tri Sumarnadi; Syafri, Ildrem; Rosana, Mega Fatimah; Zulkarnain, Iskandar (Geological Agency, 2018)
DOI: 10.17014/ijog.5.2.129-136Dieng geothermal field including its volcanic geothermal system is dominated by hot water. Brine water is characterized by high salinity, content of chloride (Cl-), amorphous silica (SiO2), Na+, and K+. The condition of brine water has potential for the formation of amorphous silica scale in the re-injection pipeline which is one of the obstacle in the electrical energy production. The scale prevention on re-injection pipes was performed with non-acid re-injection system. Nevertheless, the scale formed in the re-injection pipe is still relatively thick due to the non-optimal sludge. This research is focused in optimizing the deposition of sludge. The research aim is to apply scale prevention technique on re-injection pipeline by involving engineering technology. The study was conducted through laboratory experiments with factorial design method 23 (two levels of three factors). Those three factors are pH, concentrations of coagulants and flocculants concentrations which act as the independent variables. The indicator is the volume of sludge deposition and turbidity of brine water which act as the dependent variables. The result showed that the most significant factor is pH, whereas the concentrations of coagulant and flocculant are preserved to accelerate and stabilize the sludge deposition. The optimal condition is achieved at the level of pH 8, the concentration of 10 ppm coagulant (PAC), and 1 ppm flocculants (Polyamide). These parameters are then used for the preparation of scaling process technology on the prevention of re-injection pipeline by adding some equipments on settling ponds. Therefore, in addition to reduce environmental degradation, it also produces sludge that has potential to be used as raw materials for other industries.